2016
DOI: 10.2151/sola.2016-038
|View full text |Cite
|
Sign up to set email alerts
|

Regional Characteristics of Recent Dust Occurrence and Its Controlling Factors in East Asia

Abstract: Aeolian dust, resulting from wind erosion, is controlled by two major factors: aeolian erosivity (i.e., wind speed) and aeolian erodibility (i.e., land surface conditions). Erodibility factors include a number of land surface parameters that interact in complicated manners. Thus far, the extent to which each of the factors contributes to dust outbreaks, which vary regionally and seasonally, remains unclear. As such, we present a novel map of the controlling factors for dust outbreaks in dryland of East Asia by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 32 publications
2
31
0
Order By: Relevance
“…The ecosystem of grasslands is affected by climate change and climate variability as well as anthropogenic impacts. Wu et al [7] suggested that erodibility has a stronger effect than erosivity on dust occurrence at most stations of the steppe regions in East Asia. They conducted a simple regression analysis on DOR and each of the variables (temperature, precipitation, and NDVI) and clarified the most important influencing erodibility factor at a station scale.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The ecosystem of grasslands is affected by climate change and climate variability as well as anthropogenic impacts. Wu et al [7] suggested that erodibility has a stronger effect than erosivity on dust occurrence at most stations of the steppe regions in East Asia. They conducted a simple regression analysis on DOR and each of the variables (temperature, precipitation, and NDVI) and clarified the most important influencing erodibility factor at a station scale.…”
Section: Discussionmentioning
confidence: 99%
“…For long-term spatiotemporal characteristics, a gradual reduction in wind speed was the main cause for the decreasing trend in dust occurrence in most regions of northern China during 1960-2007 [6]. However, the responsibility of erosivity for the interannual variation in dust occurrence mainly appears in desert regions, whereas erodibility plays a more important role in other regions [7]. 2 of 13 Erodibility is the susceptibility of land surface to wind erosion and is influenced by various factors such as vegetation cover, soil moisture, and snow cover.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations